(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the essence and development of creative pedagogy and innovative educational models in the context of the post-industrial society. It highlights the transformation of education from a knowledge-transmission system to a creativity-oriented process that fosters flexibility, critical thinking, and lifelong learning. The study emphasizes the importance of integrating digital technologies, interdisciplinary approaches, and project-based learning as key mechanisms of innovation in modern pedagogy. The author proposes a conceptual framework for creative education that aligns with the socio-cultural and technological demands of the post-industrial era. The results show that creative pedagogy serves as a strategic foundation for forming human capital capable of adapting to global changes and technological progress.